2021
DOI: 10.1021/acs.jpcc.1c05378
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dark Excitons in the Excitation Energy Transfer of Carbon Nanotubes

Abstract: Excitation energy transfer (EET) between single-walled carbon nanotubes (SWNTs) and organic molecules and that between SWNTs have been extensively studied in experiments. Our first-principles calculations based on many-body Green’s function theory show that the Förster’s dipole–dipole coupling approximation fails for the EET of SWNTs, while higher multipole interactions play a major role. This means that donor–acceptor electronic coupling related to the dark excitons of SWNTs may sometimes become several orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The phenomenon of excitation energy-dependent emission (EDE) can also be named the terminologies such as red-edge effect (REE), edge excitation shift (EES), edge excitation red shift (EERS), or the red-edge excitation shift (REES). There are numerous examples of materials exhibiting the excitation wavelength-dependent emission, such as microcrystalline wide band gap aluminosilicate materials, metal complexes, anisotropic materials, and ultrathin layered nanostructures, and also many studies to unravel the solute–solvent interactions in highly rigid environments, such as viscous solvents, ionic liquids, glasses, , viscous polymers, carbon nanotubes, , graphene oxides, proteins, and membranes . Based on the types of materials, this kind of excitation wavelength-dependent photoluminescence behavior has been attributed to different photophysical processes: the dielectric effect of the trapped radiating dipole, , the pressure- and temperature-dependent emission of fluorescent tracers, the interaction between a deep defect and the tail states of subconduction band edge, the interplay of electron–photon and electron–phonon interactions, or the strain-induced radiative transition from multiple excited states .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The phenomenon of excitation energy-dependent emission (EDE) can also be named the terminologies such as red-edge effect (REE), edge excitation shift (EES), edge excitation red shift (EERS), or the red-edge excitation shift (REES). There are numerous examples of materials exhibiting the excitation wavelength-dependent emission, such as microcrystalline wide band gap aluminosilicate materials, metal complexes, anisotropic materials, and ultrathin layered nanostructures, and also many studies to unravel the solute–solvent interactions in highly rigid environments, such as viscous solvents, ionic liquids, glasses, , viscous polymers, carbon nanotubes, , graphene oxides, proteins, and membranes . Based on the types of materials, this kind of excitation wavelength-dependent photoluminescence behavior has been attributed to different photophysical processes: the dielectric effect of the trapped radiating dipole, , the pressure- and temperature-dependent emission of fluorescent tracers, the interaction between a deep defect and the tail states of subconduction band edge, the interplay of electron–photon and electron–phonon interactions, or the strain-induced radiative transition from multiple excited states .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Still, even for objects with sizes D ≪ λ, the dipole approximation (with respect to the electric multipole expansion) is known to fail to account for matter-matter interactions when the spatial gap δ between the interacting objects is smaller than their sizes. 87,89,90 We may simply illustrate this by comparing the plasmonic properties of a molecule-nanosphere system, for which the interobject gap is of the order of the molecular size, to those of a nanoparticle dimer in which the gap may be reduced far below the particle size. The first system is straightforwardly modeled in the dipolar approximation as long as D part ≪ λ, 14 whereas it is well-known that the second system requires a multipolar description of the plasmonic interaction.…”
Section: A Quadrupolar Contributionsmentioning
confidence: 99%
“…have shown that higher multipole interactions are determining, 89 favoring resonant energy transfers between dark states (i.e. dipole-forbidden) instead of bright states (i.e.…”
Section: A Quadrupolar Contributionsmentioning
confidence: 99%
“…56 However, theoretically, the physics of dark exciton in the FRET's of TMD-ML's or generic low-dimensional systems remain rarely investigated so far. 39 In this work, we study the energy transfer from donors of nanocrystal quantum dots (QD's) to an acceptor of MoS 2 monolayer (MoS 2 -ML), one of the best known TMD-ML's, as schematically illustrated in Fig. 1(c).…”
Section: Introductionmentioning
confidence: 99%